Value of Serum Lactate Dehydrogenase Level in the Detection of Hemato-oncological Malignancies and its Response to Induction in Childhood Acute Lymphoblastic Leukemia (Bangladesh Journal of Child Health, 2010)
Serum lactate dehydrogenase (LDH) level was estimated in 77 childhood (age range 1- 15 years) hemato-oncological malignancies: acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), Hodgkin's disease (HD) and Non- Hodgkin's lymphoma (NHL) on admission. Serum LDH level was also measured in ALL on day 14 and day 29 of induction. Another 25 children without hemato-oncological malignancies were included as control. On admission, the level of serum LDH was significantly raised in all hematooncological malignancies but the levels was highly significant in ALL than control (p